Recruitments, engagements, and partitions: managing participation in play. Issue 1 (2nd January 2016) - Butler, Carly W.; Duncombe, Rebecca; Mason, Carolynne; Sandford, Rachel
ABSTRACT: This paper examines the social practices children use to manage participation in play activities. Part of a wider research project looking at children's physical activity in play, this article considers the role of social interaction in shaping active play. The focus is on how children get others to take part in play they have initiated, and how inclusion and exclusion in play is managed. The data examined are video-recordings of seven- to eight-year-old children's play with toys and boxes in groups of four. The analysis identifies three interactional strategies used to manage play participation: recruitments, engagements, and partitions. We discuss the design and use of these strategies within the play activity. The paper contributes to studies of children's play interaction, and argues for the importance of understanding children's social practices in studies of physical activity in play. Implications for interventions aimed at encouraging active play are discussed.